AKUNTANSI SOSIAL: DALAM PERSPEKTIF BELIS PERNIKAHAN MASYARAKAT MANGGARAI BARAT - Wizaldy Fabiano Hilnicputro (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2022)
Problems related to accounting in an increasingly modern era today are of course also very many in relation to the series of management of these inputs, processes and outputs. When viewed more specifically in terms of accounting itself, it is actually not only about business matters. One of the problems that are rarely known together is the accounting treatment in terms of culture or customs. The buying process of the West Manggarai community basically does not have a clear and written standard of price rules and regulations, but the rules and price fixing are implied which have been going on for generations and are habitual. The main data collection technique in phenomenological studies is in-depth interviews with research subjects. The determination of belis prices in West Manggarai district is obtained through several stages such as the domain analysis stage, taxonomic analysis and component analysis that will be used to analyze the questions posed. This research proves that the price itself does not only have a final goal in the form of material or other things related to theories in accounting, especially the most important element in forming the price, but there are still many other important elements in determining it, one of which is culture. Price has a different meaning when viewed from various perspectives of the West Manggarai community, including the price as an appreciation, the price as a male and female family bond, and the price as a form of gratitude